Work Life Balance: Strategi Peningkatan Kinerja Karyawati Perbankan - Agus Peni Jaelani; Arga Sutrisna; Ari Arisman (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This research is an effort to develop employee performance, specifically among female banking employees in Bandung City. Performance development is crucial for adapting to rapid and easily accessible changes driven by Artificial Intelligence (AI). It is hoped that enhanced performance will yield a human resource capable of competing with existing technology. A further rationale for this study is the existence of prior research indicating that Emotional Intelligence does not significantly affect employee performance. The method employed to achieve these objectives is explanatory research. This approach is chosen as the researcher aims not only to describe the empirical facts observed in the field but also to analyze and explain the relationships between variables. This study was conducted with 100 female banking employees in Bandung City, selected through a sampling system. Data analysis was performed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) Version 4.1.1.6. The findings of this study are: first, there is no significant influence of Emotional Intelligence on the performance of female banking employees; second, there is a significant influence of Emotional Intelligence on Work-Life Balance; third, there is a significant influence of Work-Life Balance on the performance of female banking employees; and fourth, Work-Life Balance is proven to mediate the influence of Emotional Intelligence on employee performance.